Barriers to HIV voluntary counselling and testing among refugees and asylum seekers from African Great Lakes region living in Durban - Mujyambere, Prudence (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2012.